The Morality of Flexing: An Analysis of Unethical Recruitment Strategies in Digital Gig Economy from Religious Perspective - Elisabet Halida Wahyarsi; Arissetyanto Nugroho; Seta A Wicaksana (Indonesian Academy of Social and Religious Research (IASRR), 2026)
The rapid growth of the digital gig economy has given rise to a new and controversial profession: Binary Option platform affiliates, who frequently employ the